A Dermatologia na Enfermaria de Medicina Interna: Análise Retrospectiva de um Centro Terciário - Tomás Pessoa e Costa; Ana Luísa João; Márcia Pereira; Ana Rita Estriga; Filipa Rocha Páris; Eduardo Gomes da Silva (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Background: Skin diseases are common in Internal Medicine wards and often require observation by a dermatologist. This study intends to characterize the pattern of skin pathology in these patients and to evaluate the impact of dermatologists in their approach. Methods: A retrospective study was conducted. Dermatology observations over 46 months in Internal Medicine wards of Hospital Santo António dos Capuchos were analyzed. Patients' conditions were classified according to the 10th revision of the International Statistical Classification of Diseases and Related Health Problems. Results: 231 men and 217 women were observed, with an average age of 72.6 years. Stasis dermatitis and venous leg ulcers were the most common diagnosis. Discussion and Conclusion: The Dermatology team significantly reduced the number of undiagnosed patients. Our study reinforces the importance of dermatologists in the evaluation of inpatients with skin diseases.